Burden of Cytomegalovirus DNAemia among Pediatric Renal Transplant Patients on Antiviral Prophylaxis: A Hospital-Based Analysis. (4th October 2017) - Mehta, Kayur; Al-Yabes, Ohoud; Petrich, Astrid; Williams, Angela; Hebert, Diane; Langlois, Valerie; Allen, Upton
Abstract: Background: Cytomegalovirus (CMV) is a major cause for concern among transplant patients. Some pediatric centers employ a prevention strategy with antiviral prophylaxis and polymerase chain reaction (PCR) to monitor for CMV DNAemia in the post-transplant period. This study examines the burden of CMV DNAemia and time to such events among renal transplant patients within the first year after transplantation. Methods: We conducted a retrospective review of renal transplant patients (<18 years) who were transplanted between January 2007 and December 2012. Patients who were CMV donor-seropositive (D+) and recipient seronegative (R-) received prophylaxis with ganciclovir (IV) for 2 weeks followed by valganciclovir or oral acyclovir for 10 weeks and low-risk (D+R+ or D-R+) patients received valganciclovir for 12 weeks, with modifications based on age and clinical status. Clinical and laboratory data were obtained from the medical records and laboratory databases. Results: Among 121 patients, the median age at transplant was 12.6 years (range 6 months–17.8 years); M:F ratio 1:0.57. Forty-two patients (34.7%) received anti-T-cell globulins. CMV serostatus: D+R- 27 (23.1%); D-R+ and D+R+ 35 (29.9%) and D-R- 55 (47%). CMV DNAemia was detected in 18 patients (14.8%) during the first post-transplant year. Among these patients, 8 were D+R- and 8 were D-R+ or D+R+. Median time to first positivity was 134 days (range 0–188 days). Among patients whose first positive PCR was after 3 months post-transplant, median time to positivity was 53 days (range 32–98 days) after the end of prophylaxis. Conclusion: CMV DNAemia while on prophylaxis was uncommon, occurring 1 in 40 transplanted patients. Routine monitoring while on prophylaxis may be no longer warranted. Studies are needed to determine the optimal indications for CMV PCR testing while on prophylaxis. Disclosures: All authors: No reported disclosures.